2020
DOI: 10.7554/elife.56996
|View full text |Cite
|
Sign up to set email alerts
|

A missense in HSF2BP causing primary ovarian insufficiency affects meiotic recombination by its novel interactor C19ORF57/BRME1

Abstract: Primary Ovarian Insufficiency (POI) is a major cause of infertility, but its etiology remains poorly understood. Using whole-exome sequencing in a family with 3 cases of POI, we identified the candidate missense variant S167L in HSF2BP, an essential meiotic gene. Functional analysis of the HSF2BP-S167L variant in mouse showed that it behaves as a hypomorphic allele compared to a new loss of function (knock-out) mouse model. Hsf2bpS167L/S167L females show reduced fertility with smaller litter sizes. To obtain m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 65 publications
6
60
1
Order By: Relevance
“…More recently, five groups independently reported that HSF2BP interacts with an uncharacterized protein named C19orf57, 4930432K21Rik, BRME1 , MEIOKE21, or MAMERR. The two proteins co-localize in meiocytes, loss of BRME1 closely phenocopies loss of HSF2BP, and the two proteins can affect each other’s stability 22 – 26 . The model put forward to explain the meiotic defects in knock out mice for either Hsf2bp or Brme1 follows the PALB2 paradigm: HSF2BP and BRME1 are proposed to act as “meiotic localizers” for BRCA2—and for each other 25 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, five groups independently reported that HSF2BP interacts with an uncharacterized protein named C19orf57, 4930432K21Rik, BRME1 , MEIOKE21, or MAMERR. The two proteins co-localize in meiocytes, loss of BRME1 closely phenocopies loss of HSF2BP, and the two proteins can affect each other’s stability 22 – 26 . The model put forward to explain the meiotic defects in knock out mice for either Hsf2bp or Brme1 follows the PALB2 paradigm: HSF2BP and BRME1 are proposed to act as “meiotic localizers” for BRCA2—and for each other 25 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this hypothesis, Hsf2bp ( Brandsma et al, 2019 ; Zhang et al, 2019 ) and (to a lesser extent) Brme1 knockout mice ( Zhang J. et al, 2020 ; Felipe-Medina et al, 2020 ; Shang et al, 2020 ) show a strong reduction in meiotic recombinase RAD51/DMC1 foci numbers, associated with severe meiotic defects in males. Interestingly, these proteins are critical only for male fertility while their absence in females has only minor consequences ( Zhang et al, 2019 ; Brandsma et al, 2019 ; Felipe-Medina et al, 2020 ; Shang et al, 2020 ; Takemoto et al, 2020 ; Zhang J. et al, 2020 ). This suggests that recombinase loading might be differentially regulated in female mice.…”
Section: Regulation Of Recombinase Assembly At Meiotic Dsbsmentioning
confidence: 56%
“…In this review, we provide an overview of recent data on RAD51 and DMC1 recruitment, which raises several key issues. First, the recently discovered meiotic proteins HSF2BP and BRME1 are critical for BRCA2-mediated loading of RAD51 and DMC1 ( Zhang et al, 2019 ; Zhang J. et al, 2020 ; Brandsma et al, 2019 ; Felipe-Medina et al, 2020 ; Shang et al, 2020 ; Takemoto et al, 2020 ). However, key evidence that directly couples BRCA2 localization and activity to that of HSF2BP and BRME1 is still missing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations